KONSUMERISME DAN KORUPSI: PERSPEKTIF BUDAYA DAN HUKUM - Mawar Sitohang; Petrus CKL Bello (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study analyzes the complex relationship between consumer culture and corrupt practices, using legal perspectives from the perspectives of cultural studies and law. Consumer culture, driven by an excessive desire for material possessions and social status, creates psychological and social pressures that can trigger corrupt acts. Culturally, consumerism encourages a shift in values from collective ethics to materialistic individualism, where success is often measured by wealth. As a result, people easily slip into corrupt lifestyles such as committing fraud, accepting gratuities/bribes, and so on. This legal research aims to provide a deeper understanding of the roots of corruption, which are not only structural but also cultural. This study finds that the phenomenon of consumption has become a culture, from the birth of consumer culture to the contradictions within consumer culture. It also discusses the relationship between consumer culture and corrupt lifestyles